Brainstem haemorrhage as a rare complication of burr hole craniostomy - Rodolfo Corinaldesi; Corrado Filippo Castrioto; Francesca Romana Barbieri; Luciano Mastronardi; Umberto Ripani (Medicinski glasnik, 2020)
Aim: Evacuation through burr hole craniostomy is the most common type of chronic subdural hematoma surgical treatment, with a morbidity rate of 0-9%. Methods: Here we present a case of 66-year-old Caucasian woman with bilateral hemispheric chronic subdural hematoma and left transtentorial uncal herniation. Bilateral burr hole craniostomy with gradual and simultaneous evacuation was performed and subdural drains were placed with daily strict monitoring of drained fluid. Results: Despite immediate prompt neurological improvement, on the second postoperative day bilateral ptosis and left medial rectus weakness occurred, with no signs of consciousness deterioration. Radiological exams revealed a 9 x 6 mm haemorrhage of the tegmentum mesencephali. In the next day progressive neurological improvement occurred and a follow-up at 1 month revealed persistence of bilateral ptosis with almost complete regression of the left medial rectus weakness. Conclusion: Although burr hole craniostomy is considered a minor procedure, rare but fatal complications like brainstem haemorrhage may occur. Bilateral simultaneous and gradual drainage, strict monitoring of drained fluid and blood pressure in the perioperative period and frequent neurological with prompt radiological assessment in case of clinical worsening, should be the mainstay of a correct management of chronic subdural hematoma (particularly if bilateral) in order to avoid potentially fatal complications.
Keywords: bleeding; chronic subdural hematoma; clinical worsening; post-surgical issue; surgical procedure